Designing justice? Race and the limits of recognition in greater Miami resilience planning. Issue 117 (December 2020) - Grove, Kevin; Barnett, Allain; Cox, Savannah
Highlights: Equity-oriented resilience struggles to address place-specific histories of racism. Multiple forms of recognition impact urban resilience in contradictory ways. Design-driven resilience enhances recognition but can also reinforce anti-Blackness. Addressing justice requires inductively engaging racialized politics of recognition. Abstract: This paper explores the relation between resilience, justice and recognition through a case study of resilience planning in the Greater Miami Region. Greater Miami resilience plans, prepared through the Rockefeller Foundation's 100 Resilient Cities program, have foregrounded equity as a cross-cutting theme – a surprising move given the region's history of anti-Black violence, segregation, and racially exclusionary governance, and the recent focus of resilience-building initiatives on sustaining property values. Bringing together literatures on resilience and justice, recognition, critical race theory, and design theory, we ask how Miami resilience initiatives extend the structures of anti-Black violence through efforts to address the region's extreme racial and economic inequalities in the name of equity and shore up the regional economy against complex socio-ecological shocks and stressors. Our analysis details how Miami's resilience-building efforts are uneasily situated across at least two distinct styles of recognition. On the one hand, contextually-specific norms of recognition shaped through the region's history of racial capitalism valorize the security of Miami's racialized real estate markets. On the other hand, design-driven resilience planning initiatives valorize diverse forms of knowledge on racially uneven development for the pragmatic utility they offer planners and professionals seeking holistic solutions to complex socio-ecological problems. While designerly approaches to resilience-building have created new possibilities for incorporating equity concerns (promoted by local social and climate justice organizations) into decision-making processes, they ultimately fail to unsettle the libidinal economy of dehumanizing anti-Black violence that continues to structure who can author(ize) what a resilient Miami might become.